Advantages and Disadvantages of Distance Learning in Universities - Kotrikadze, Elena Vazhaevna (2021)
Distance learning has always been of interest to researchers and scientists since its inception. In the current environment of the modern world, this type of training is becoming increasingly popular despite the large number of its opponents. Of course, it can not be called absolutely perfect, because it requires the availability of impeccable technical equipment of educational institutions, uninterrupted Internet, a perfectly working portal and an appropriate platform for such training. The Article is devoted to the description of the advantages and disadvantages of learning in higher education. In the context of modern realities, distance learning is spreading faster and faster in all areas of our life, in particular in the educational process. However, it cannot completely replace traditional learning. There is no doubt that distance learning has a number of advantages, but in view of the lack of uninterrupted Internet outside of large cities, and sometimes its complete absence, there are many problems regarding the organization of this type of training. It should also be noted that distance learning requires a lot of self-discipline of a person and the ability to independently study a particular subject. Therefore, before making a decision to completely replace traditional distance learning, it is necessary to weigh all the pros and cons, remembering that distance learning cannot be perfect enough and that it cannot be a worthy replacement for traditional learning.